Kebijakan Pendidikan di Era Globalisasi - Subayil Subayil (Misykat al-Anwar Jurnal Kajian Islam dan Masyarakat, 2020)
ABSTRACTEducation policy is a comprehensive measure related to the time devoted to what and who the policy is made for. So that the existence of educational policies has a positive effect on all dimensions of life that are related to education itself, starting from the input process to the output process of the educational activity itself. And in the end, education policy is not only a periodic political policy agenda. However, education policy itself does have a significant impact on the development of education in the current era of globalization.Keywords : Education Policy, Globalization Era, and Quality of Human Resources.